Investigating Right Wing Authoritarianism With a Very Short Authoritarianism Scale - Boris Bizumic; John Duckitt (Journal of Social and Political Psychology, 2018)
Authoritarianism has been an important explanatory concept for more than 60 years and a powerful predictor of social, political, and intergroup attitudes and behaviour. An important impediment to research on authoritarianism has been the length of the measures available, particularly with the contemporary emphasis on the need for social research to use larger, more representative samples and measure multiple constructs across multiple domains. We therefore developed a six-item Very Short Authoritarianism (VSA) scale that equally represented the three content subdimensions and two directions of wording of Altemeyer’s widely used Right Wing Authoritarianism (RWA) scale. Over four samples (N = 1,601) from three countries the VSA scale showed satisfactory internal consistency and the expected hierarchical factor structure with three primary factors loading on a single higher-order factor. Additionally, the scale predicted variables such as nationalism, ethnocentrism, political orientation, political party/candidate support, attitudes towards ingroups or outgroups and anti-minority bias at moderate to strong levels with effects very close to those obtained for much longer established measures of RWA (including Altemeyer’s scale). The VSA scale also showed clearly better reliability and validity than a short measure of authoritarian parental values that has been used to measure authoritarianism.